Negotiation and constraint: analyzing Scottish nationalism within Britain an EU - Chambers, Gary C. (My University, 2005)
For most of the twentieth century, it seemed as if the problem of national identity had been conclusively resolved in the universal promise of the modern nation state from which people derived a range of economic, social, psychological and cultural benefits. 'Identity politics' were regarded as atavistic, retrograde and occupied minimal or negligible space on the political agenda. Minority nationalisms are clearly the product of highly varied historical experiences and also articulate demands for self-determination in different ways. A vital part of the new British political geography is the resurgence of nationalism in Scotland and Wales and the apparently irrecoverable decline of British Unionism. Therefore, this thesis seeks to analyze the historical, political, economic and cultural development of the Scottish nation, to critically examine the challenge posed by the demands of Scottish nationalism (or their absence) from the early years of the eighteenth century to the present and examine how the British state has sought to respond to (or ignore) these demands. In this way, the thesis will seek to illuminate the circumstances, which Scotland has confronted in attempting to exercise autonomy and how Scottishness has become a prioritized form of national identity. Thus, this thesis will argue that the Scottish case should be seen as a laboratory, as a source of innovation, for new political arrangements which redefine the traditional nation-state and in which shared and limited autonomy between different levels of government -Scottish, British and European -become more commonplace.

Ulusal kimlik sorunu, yirminci yüzyıl boyunca insanların kendilerine ekonomik, toplumsal, psikolojik ve kültürel çıkarlar sağlayan modern ulus devletin gelişen olanaklarıyla çözülmüş gibi görünmüştür. 'Kimlik politikaları' ulusun atalarına dayanmakta ve geçmiş çağlara dönüş eğilimi taşımaktadır. Siyasal gündemde çok az yer tutuyordu. Azınlık milliyetçiliği, çok çeşitli tarihsel yaşantıların ürünüdür. Aynı zamanda azınlık milliyetçiliğinin kendi geleceğini belirleme (self-determinasyon) konusunda değişik istemeleri vardır. Yeni Britanya siyasal coğrafyasının yaşamsal bir parçası olan İskoçya ve Galler'de milliyetçilik yeniden uyanmaktadır. Britaniya'nın birliği görünüşte geri dönülmez bir çöküş yaşıyor. Söz konusu nedenlerden dolayı bu tez, İskoç halkının tarihsel, siyasal, ekonomik ve kültürel değişimin analiz etmeye çalışıyor. Bu tezi on sekizinci yüzyıl başlarından günümüze İskoç milliyetçiliğinin (veya bunun yokluğunun) getirdiği istemlerin yarattığı tartışmaya eleştirel olarak bakmayı ve Britanya devletinin bu istemlere yanıt vermek (veya bunları dikkate almamak) konusunda nasıl yollar aradığını çözümlemeyi amaçlamaktadır. Bu şekilde tez, İskoçya'nın özerkliğini elde etme çabasını ve İskoçyalılığın bir ulusal kimlik olarak nasıl öne çıktığını tartışmaktadır. Dolayısıyla bu çalışma, değişik hükümet düzeyleri arasında - İskoç, Britanyalı ve Avrupalı-paylaşılan sınırlı özerkliği içinde barındıran geleneksel ulus-devleti yeniden tanımlayacktır. Bu tanımlamayı içeren yeni siyasal düzenlemeler için İskoçya olgusu bir laboratuvar, hatta öncü olarak görülmelidir.
Keywords: Azınlık Milliyetçiliği_Britanya; Milliyetçilik; Nasyonalizm; Siyasal bilimler (Siyaset bilimi); Siyasal ideolojiler; Toplum bilimleri; Ulusal Kimlik_İskoçya